INVENTORY MANAGEMENT AND STAKEHOLDER’S RETURN ANALYSIS IN HIGH TECHNOLOGY INDUSTRIES - Anita Munir, M.Fin (Journal of Management and Leadership, 2018)
High technology industry is one of the fastest growing industries in the world. The adequate and timely movement stocks are imperative for these companies to growth and achieve financial success. This study employs regression analysis to investigate the impact of inventory management on return to stakeholder of high technology industries. The population consisted of the seven technology industries listed under the manufacturing sector in the world stock exchange. Simple random sampling was employed in sample selection. Information for the study was taken from secondary sources, specifically, the audited financial statements of the high technology companies for the period 2011 to 2016 financial years with a total of 42 samples. Return on equity that related to return on stakeholder as dependent variable was used as a proxy for profitability, while independent variable of inventory turnover was used as a proxy for inventory management; and independent variable of quick ratio represented the control variable. Findings from the analysis revealed the existence of statistically significant relationship between stock management and profitability of technology industries and negative relation with financial quick ratio.